The Legal Formulation of Marital Joint Property Disputes over Encumbered Assets Based on Maqāṣid al-Sharīʿah and Its Implications for Islamic Legal Education - Sobardi, Ahmad; Rosidi, Imron; Jamal, Khairunnas; Khabibjonovna, Kushieva Nodira (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study examines the doctrinal and practical dilemma created by Supreme Court Circular Letter (SEMA) No. 3 of 2018, which directs courts to declare inadmissible claims for marital joint property when the disputed asset remains encumbered as debt collateral. While intended to protect creditors and preserve legal order, a rigid inadmissibility doctrine may delay or effectively deny spouses’ entitlement to jointly acquired assets and weaken access to substantive justice in Religious Court practice. Using normative legal research that combines philosophical, statutory, case-based, comparative, and historical approaches, this study analyzes primary, secondary, and tertiary legal materials through prescriptive reasoning, legal hermeneutics, and a maqāṣid al-sharīʿah–informed ijtihād framework. The findings show that the ratio legis of SEMA No. 3/2018 rests on preventing overlapping legal interests, upholding nemo plus iuris, avoiding adjudication over imperfect ownership (al-milk al-tāmm), and safeguarding creditors’ preferential rights. However, these aims can be preserved without foreclosing spousal claims. Accordingly, this study proposes a refined legal formulation: courts may grant claims over encumbered marital joint property while deferring distribution and execution until the secured debt is fully satisfied. This reformulation strengthens legal certainty and equitable protection by clarifying procedural requirements and substantive criteria, and it also highlights the pedagogical value of maqāṣid as an integrative paradigm for Islamic legal education that cultivates contextual reasoning, normative responsibility, and case-based analytical competence among future jurists.